Pendampingan Penyusunan Usulan Penetapan Dam Cluwok (Kersluit Gesikan) sebagai Bangunan Cagar Budaya di Kabupaten Tulungagung - Latif Kusairi; Moh Ashif Fuadi; Irma Ayu Kartika Dewi; Nor Huda; Moh Mahbub; Aan Ratmanto; Qisthi Faradina Ilma Mahanani (Yayasan Abdurrauf Cendekia Nusantara, 2026)
service project aims to encourage the designation of Dam Cluwok (Kersluit Gesikan) as a Cultural Heritage Building in Tulungagung Regency. This structure is a legacy of Dutch colonial infrastructure that holds historical, technological, and social significance, particularly in the system of water management and irrigation. In addition to functioning as a water flow control structure, Dam Cluwok represents the development of colonial hydraulic engineering that continues to provide benefits for the surrounding community. However, the lack of public awareness and the absence of official designation as a cultural heritage site make this structure vulnerable to damage and the loss of its historical significance. The implementation method employs a participatory approach involving the local community, the Tulungagung Regional Government, the Cultural Heritage Expert Team, historians, and other relevant stakeholders. The activities include the identification and documentation of the structure, socialization of cultural heritage values, and assistance in the process of proposing its designation. The results indicate an increased public understanding of the importance of preserving cultural heritage, as well as the growth of collective support for the designation of Dam Cluwok as a Cultural Heritage Building. This project underscores the importance of collaboration between the community and the government in maintaining the sustainability of local historical heritage.